Comparing the pros and perks of hydroponic farming versus traditional agriculture - Sati, Bipin Kumar; Sharma, Vaishali; Pant, Durgesh (Indian Farming, 2023)
Hydroponics is a contemporary farming technique that doesn’t rely on soil and instead supplies plants with nutrient-rich water. In contrast, traditional farming is a soil-based approach that yields limited crops while utilizing substantial amounts of water for irrigation and fertilizers. One advantage of hydroponic farming over traditional methods is the ability to practice vertical farming, which increases crop yields per unit area. Moreover, hydroponics doesn’t require fertile land to be effective and requires less water and space compared to traditional soil-based agriculture. This research aims to explore and compare traditional farming and hydroponic farming methods in terms of their efficiency, sustainability and overall impact on the environment and food production.